In vivo digestibility of six selected fodder species by goats in northern Ghana - Avornyo, Franklin K.; Partey, Samuel T.; Zougmoré, Robert B.; Asare, Sylvester; Agbolosu, Anthony Amison; Akufo, Naana Mintaah; Sowah, Nicholas Adjetey; Konlan, Solomon Pigangsoa (Springer, 2020)
An in vivo digestibility trial was conducted to evaluate the digestibility of six forages. These were selected indigenous browse species and groundnut haulms in Lawra and Jirapa Districts of the Upper West Region of Ghana. Groundnut haulms served as a control due to its known good digestibility in small ruminants. Thirty West African Dwarf (WAD) young castrated billy goats with a mean age of 8 months were used. The average live body weight was 8.9 ± 0.1 kg. The animals were randomly assigned to the six treatments and replicated five times in a completely randomized design. They were confined in metabolism cages. The adaptation period was 3 weeks after which data was taken for 10 days. The treatments were the leaves and tiny twigs of T1 Annona senegalensis, T2 Ficus gnaphalocarpa, T3 Pericopsis laxiflora, T4 Pterocarpus erinaceus, T5 Afzelia africana, and T6 (control) Arachis hypogaea. Feed intake, faecal matter and urine output were measured. The results indicated that dry matter (DM) contents of the feedstuffs were less than 50% but crude protein (CP) contents were higher than the minimum required for sustaining ruminants. Neutral and acid detergent fibre contents were high, and F. gnaphalocarpa, in particular, contained a higher level of phosphorus (P). The amounts of feed intakes were typical of most fodder species with the exception of P. laxiflora and P. erinaceus, which were lower (P < 0.05). The apparent digestibility values were also typical of most fodder species but the digestibility of A. africana fibre appeared to be lower. Nitrogen retention was positive for all test species with the exception of P. laxiflora, which was negative. Mortality was recorded in animals on P. laxiflora, and the rate was high. Pericopsis laxiflora leaves, even though morphologically similar to the leaves of P. erinaceus, were not a suitable fodder. Ficus gnaphalocarpa appeared to be the overall best fodder species in terms of nutrient uptake.